An Expert System To Determine The Bone Diseases - Md. Rifin, Shuhada (Universiti Teknologi Petronas, 2004)
An expert system named BONNEX to diagnose bone diseases, being one of artificial intelligence (AI) applications, has been developed in this work. This expert system is utilizing the expertise from orthopedics and other resources. BONNEX is used to perform diagnoses based on patient's data, clinical examination data and other relevant sources in the same way as an expert can do. With the help of the expert system, the non experts can perform the decision making process in the same wayas the experts. BONNEX would make experts' diagnostic capability more widely available in the clinical community. BONNEX will aid inexperienced orthopedics or general practitioners working in small medical centers and rural areas to diagnose the nature and conditions of the bone diseases amongst patients before it can be referred to the expert doctors and orthopedic who will be normally be available in the big hospitals or medical centers which are far away from patients' location. It is hoped that with the early detection of the bone diseases, further and immediate therapies can be taken to cure the diseases The elements needed in developing the expert system are user interface, database, knowledge base, explanation facility and inference engine. The users interact with the system through a user interface. The database of the system contains expert-level knowledge on bone diseases and the information is obtained from interviews with the expert orthopedics and research from books, websites and journals. After the bone diseases are determined, the signs and symptoms of the diseases are verified and classified into three categories. The data is re-arranged into systematic representation. The decision table is prepared for the system. The decision table is the representation of the findings to ease the expert system development. It lists out the diseases in one axis and the corresponding symptoms into another axis.